MICROANALYSIS OF δ13C, δ15N, AND N ABUNDANCES IN DIAMONDS BY SECONDARY ION MASS SPECTROMETRY - Hauri E.H.; Wang J.; Pearson D.G.; Bulanova G.P. (My University, 2002)
This paper describes in situ analysis methods for determination of nitrogen abundance, δ13C, and δ15N in diamond by secondary ion mass spectrometry (SIMS). The simple chemical composition of diamond results in the absence of matrix effects on instrumental mass fractionation (IMF) of carbon and nitrogen. Carbon isotopes are analyzed using extreme energy filtering (EEF), while nitrogen abundance and isotope ratios are measured at high mass resolution (HMR) without energy filtering. Because the variable surface properties of different sample mounts can result in variable measurements of IMF, especially using HMR techniques, precise application of IMF values derived from standard measurements requires the co-location of standards and samples on the same probe mount. With care given to instrument alignment and standardization, δ13C in diamond can be determined to ± 0.3‰ (1σ) total uncertainty (precision + accuracy). Reproducibility of δ15N measurements can be as good as ± 1‰ (1σ) depending on N abundance, but standard heterogeneity currently limits the accuracy of δ15N data to ± 3‰ (1σ). Nitrogen abundance measurements, obtained during δ15N measurements, have an accuracy of ± 10% and a detection limit of 0.5 ppm. The 25-μm spatial resolution of this technique permits isotopic measurements at the scale of diamond growth zoning observed by cathodoluminescence (CL) imaging. Measurements on a central polished section of a Siberian diamond show variations in δ13C ( - 8.8‰ to + 1.7‰), δ15N ( - 17.1‰ to + 5.3‰) and N abundance (14-1390 ppm) associated with CL-imaged growth zones, which span a significant fraction of the total isotopic variability observed in bulk analyses of individual diamonds. In situ δ13C, δ15N, and N abundance measurements, in conjunction with CL imaging and FTIR N aggregation measurements, hold promise for determining the extent of isotopic variability which can be attributed to diamond formation processes, and the significance of isotopic variability in diamonds to large-scale mantle heterogeneity and the origin of terrestrial volatiles.